The Effectiveness of AI Technology in Improving Academic English Writing Skills in Higher Education - Veri Hardinansyah Dja'far; Fitria Nur Hamidah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The main issue in improving academic writing skills in English among college students is the difficulty in developing coherent and grammatically accurate writing. The aim of this research is to evaluate the effectiveness of using AI-based technology in enhancing students' writing abilities and addressing gaps in traditional teaching methods that often lack personalized feedback due to limited teaching time. This research employs a mixed-method approach, combining quantitative pre-experimental design and qualitative methods. The study uses an experimental design with control and experimental groups consisting of students from classes 1A and 1B. A pre-test was conducted, followed by three writing assignments over seven weeks, with the experimental group receiving AI feedback. The results show a significant improvement in the writing skills of the experimental group, with average scores increasing from 1204 to 1364, a statistically significant difference (p <0.05). Additionally, this study also explores students' perceptions and attitudes towards AI tools, providing insights into the acceptance and effectiveness of such tools in diverse educational environments. It can be concluded that the integration of AI-based tools in teaching academic English writing significantly improves students' writing skills. The integration of AI in English writing instruction can be an effective solution to address teaching challenges and enhance the quality and effectiveness of learning. This research recommends a wider application of AI technology in education to support the development of students' writing skills.